Chronic pain conditions and depression in the Ibadan Study of Ageing (2011)
"Background—Chronic pain is quite common in the elderly and is often associated with co morbid depression, limitation of functioning and reduced quality of life. The aim of this study was to ascertain whether there is a differential risk of depression among persons with pain in different anatomical sites and to determine which pain conditions are independent risk factors for depression. Methods—Data is from the Ibadan Study of Ageing (ISA), a community based longitudinal survey of persons aged 65 years and older from eight contiguous Yoruba Speaking states in Nigeria (n = 2152). Data was collected in face-to-face interviews; depression was assessed using the World Mental Health initiative version of the Composite International Diagnostic Interview (CIDI) while chronic pain was assessed by self-report (response rate = 74%). Results—Estimates of persistent pain (lasting more than 6 months), in different anatomical sites range from 1.3% to 12.8%, with the commonest being joint pains (12.8%), neck or back (spinal) pain (7.6%) and chest pain (3.0%). Significantly more pain conditions were reported by females and by respondents who were aged over 80 years. The risk for depression was higher in respondents with spinal, joint and chest pain. However, only chest pain was independently associated with depression after adjustments were made for pains at other sites and for functional disability. Conclusion—Our data suggests that, among elderly persons, there is a differential association of depression with chronic pain that is related to the anatomical site of the pain."